Increasing the species diversity in the Aspergillus section Nidulantes: Six novel species mainly from the indoor environment - Sklenář, F; Jurjević, Ž; Peterson, S W; Kolařík, M; Nováková, A; Flieger, M; Stodůlková, E; Kubátová, A; Hubka, V (Mycologia, 2020)
Aspergillus section Nidulantes encompasses almost 80 homothallic and anamorphic species, mostly isolated from soil, plant material, or the indoor environment. Some species are clinically relevant or produce mycotoxins. This study reevaluated the species boundaries within several clades of section Nidulantes. Five data sets were assembled, each containing presumptive new species and their closest relatives, and phylogenetic and phenotypic analyses were performed. We tested the hypotheses that the newly isolated or reexamined strains constitute separate species (splitting approach) or should be treated as part of broadly defined species (lumping approach). Four DNA sequence loci were amplified, internal transcribed spacer (ITS) and large subunit (LSU) regions of the rDNA and partial sequences of the β-tubulin (benA), calmodulin (CaM), and RNA polymerase II second largest subunit (RPB2) genes. The latter three loci were used for the phylogenetic analysis and served as input for single-locus (GMYC, bGMYC, PTP, and bPTP) and multilocus (STACEY and BP&P) species delimitation analyses. The phenotypic analysis comprised macro- and micromorphology (including scanning electron microscopy) and comparison of cardinal growth temperatures. The phylogenetic analysis supported the splitting hypothesis in all cases, and based on the combined approach, we propose six new species, four that are homothallic and two anamorphic. Four new species were isolated from the indoor environment (Jamaica, Trinidad and Tobago, USA), one originated from soil (Australia), and one from a kangaroo rat cheek pouch (USA).
Keywords: species delimitation; indoor fungi; multispecies coalescent model; Emericella; Genes, Fungal; Australia; Aspergillus nidulans; 6 new taxa; multilokusová sekvenční typizace; Jamajka; Austrálie; sterigmatocystin production; Phylogeny; geny hub; Trinidad and Tobago; Aspergillus; Spojené státy americké; multigene phylogeny; Jamaica; United States; Trinidad a Tobago; Multilocus Sequence Typing; fylogeneze